1987
DOI: 10.1116/1.574476
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-enhanced chemical vapor deposition SiN films: Some electrical properties

Abstract: Effect of rapid thermal annealing treatment on electrical properties and microstructure of tantalum oxide thin film deposited by plasmaenhanced chemical vapor deposition Effect of power on interface and electrical properties of SiO2 films produced by plasmaenhanced chemicalvapor deposition Electrical and structural properties of rapid thermally annealed borondoped silicon films deposited by plasma enhanced chemicalvapor deposition Experimental data are presented on the effects of varying deposition parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…At the 60W condition as discussed with Fig. 8, atom percent H by infrared was 20% lower than at 18W (20 a]o vs. 24, not shown in Fig. 10a).…”
Section: Film Deposition Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…At the 60W condition as discussed with Fig. 8, atom percent H by infrared was 20% lower than at 18W (20 a]o vs. 24, not shown in Fig. 10a).…”
Section: Film Deposition Resultsmentioning
confidence: 72%
“…Dielectric properties that have been reported include resistivity (p), breakdown voltage (Eb), and the rate of trapping of injected charge at deep gap states, which is characterized by the flatband voltage shift (iV) of a MIS capacitor after electrical stressing. It turns out that these dielectric properties all improve in the process directions which correlate with increasing x. Eb and p increase with both NHjSiH4 (17) and RF power (23,24). Eb also increases with [N--H]/[Si--H] (18), and p increases with both x (25) and [N--H]/[Si--H] (26).…”
Section: Discussionmentioning
confidence: 97%
“…Besides 0 parameter, t and " d were nearly identical to the reported values for the thicker SiN capacitors. 7,16,17) Hugon et al reported that the SiN capacitor with less than 20-nm-thick film did not showed P-F conduction, however, we found that the Ta-covered TiN BE extended the thickness range for P-F conduction down to 10 nm thickness.…”
Section: Electrical Propertiesmentioning
confidence: 51%
“…It is well-known that the P-F conduction dominates the leakage mechanism in the SiN capacitor, where the SiN thickness exceeds 20 nm. 7,[16][17][18] The P-F conduction was expressed as…”
Section: Electrical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation